Evaluation Of The Supplementation Of Bitter Melon Flour (Momordica charantia) As A Feed Additive To Physical And Chemical Content Of Broiler Meat - Roselin Gultom; Lidya Amallia Ilmania; Korbinianus Feribertus Rinca; Yohana Maria Febrizky Bollyn; Maria Tarsisia Luju; Puspita Cahya Achmadi (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2023)
The purpose of this research was to evaluate the supplementation of bitter melon flour as a feed additive on the physical (tenderness and WHC) and chemical (protein and fat content) quality of broiler meat. The material used in this study was a broiler Lohman strain produced by PT. Japfa Comfeed Indonesia Tbk., unsex, and rearing for 35 days. This research method used a field experiment with 6 treatments with 5 replications. Each experimental unit was given basal feed treatment with the addition of antibiotics (Zinc Bacitracin 0.01%) (P0), 0% bitter melon flour (P1), 0.25% bitter melon flour (P2), 0.5% bitter melon flour (P3), 0.75% bitter melon flour (P4), and 1% bitter melon flour (P5). Data were analyzed with Analysis of Variance and continued with Duncan's Multiple Range Test if there were significant differences. The results showed that the addition of bitter melon flour as a feed additive didn't show a significant difference (P>0.05) in tenderness, Water Holding Capacity, protein content, and fat content of broiler meat. The conclusion of this study was that the addition of bitter melon flour as a feed additive showed relatively similar abilities to produce the physical and chemical quality of meat with antibiotics used as a feed additive for broilers.